Hands on developing your differential diagnostic skills, a workbook for demonstrating continuing professional development - Browning, Simon (Tfm Pub., 2006)
Divided into sections, each dealing with a different aspect of the consultation process, covering the general observation of the patient, aspects of the case history, physical evaluation and specific systemic examination procedures. This workbook forms a part of the therapist's continuing professional development portfolio.